JAYAPURA DALAM TRANSFORMASI AGAMA DAN BUDAYA MEMAHAMI AKAR KONFLIK KRISTEN-ISLAM DI PAPUA - , Idrus Alhamid ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia, a country with flourished natural resources, has been underpinning various and repeated societal conflicts, which detrimentally affected from the accumulation of huge unresolved problems, which gradually spreading into the grassroot of society. In Papua and Jayapura in particularly, probably one of the regions, which has experienced several societal conflicts, rooted from diverse identity issues and will be mounted up in religious conflict. Given that demographically, the composition of religious believers in Jayapura relatively equal in case of number, it has very often provoked claims from each group to declared them as the true owner of the land (Papua), and coincident with rapid people migration into Papua, which are accidently majority are Moslem that has also brought anxiety to the local inhabitants which are majority Christian believers. As the result, it has emerged social frictions between the native Papuan and the migrants in Jayapura, and placed religions (Christian and Islam) as the scapegoat of the problem. This frictions then become the furthest problems highlighted over Papua, as the religious spaces has been politicized into conflict arena which prone to any forms of inter-religious conflict in Papua. To understand this complex situation, this study through Peter L. Berger and Thomas Luckmann âs viewpoint of social construction, which argued that society, is a social reality, which being constructed in some ways. In this case, religion as a real political means, it also as a means constructed to gain interests of certain groups of society. Within this study, the data was collected through the ways of qualitative approach which are observation, interview, focused group discussion and documentation studies. The observation was held in some places in Papua and it was emphasized on the patterns of religious relationship in society, meanwhile the interview was focused on some authorized persons related to the research purposes such as government and religious elites, community leaders, youth leaders and other. To gain more insights, however the focused discussion and the documentation analysis were conducted to support each other, and in particularly, the documentation besides sought other important documents, it was scrutinized on historical documents. As the result, the study then reveals three fundamental findings. Firstly, the research suggested that religious conflict in Papua and for Jayapura in particularly looks critical in it forms when the claims from group of Christian and Moslem is much preferable to dialogical approach which indeed can be solved. The tensions between religious groups are very strongly found in wider society